(untitled) (Journal of Creative Industry and Sustainable Culture, 2023)
In this advanced society, people are inseparable from technology. Smartphones, tablets, computers, TVS have all become necessities for modern people. The way we use media has recently changed dramatically. The purpose of this research is to study the intention of escapism on binge-watching among Penangites. Video on demand allows viewers to watch anytime and anywhere because of modern technology breakthroughs. More and more viewers are choosing to enjoy the video by subscribing to streaming services or online rather than on conventional broadcast networks. The rise of binge-watching is a result of technological advancement which has resulted in a shift away from routine programming and towards more flexible viewership. Despite the fact that there are severalresearchers who have performed in diverse contexts, only a few studies have focused on the intention of binge-watching among Malaysians, particularly Penangites. This conceptual study examines previous research and aims to study the intention of escapism binge-watching among Penangites. There were 200 respondents from Penang using the Raosoft sample size calculator and they were given online survey questionnaires as part of a quantitative research project. The acquired data were then examined in SPSS to determine the correlations (Pearson’s coefficient) and reliability (Cronbach’s Alpha). The result of the study indicates that most of the respondents show a positive view of the factor of escapism affecting their desire to binge-watch. It can be seen that the majority of the respondents agree that binge-watching may help them to escape from everyday life, seek relief from the unpleasant reality of everyday life, help them to temporarily get away from the grind, immerse themselves in the unreal world as well as give them more pleasure than other activities. Other than that, this research may help in showing that new advancements in media entertainment and the ensuing alterations in usage patterns bring opportunities as well as obstacles to media consumers. In addition, it may also help in future research to gain a deeper understanding of binge-watching as a novel form of media enjoyment as well as fresh perspectives on the intricate relationship between well-being and media use in general.